(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article attempts to understand and present the diverse perspectives around same sex marriage debate in Kerala, the first state in Indiato implement state transgender policy. Drawing on in-depth field data from five self-identified homosexual individuals across different caste, class, religious, and gender backgrounds, the study foregrounds the intersectionality that shapes their perspectives on the institution of marriage.The national debate around same-sex marriage has gained increased legal and media attention, this study attempts to explore diverse perspectives from within the queer community that question the heteronormative assumptions embedded in the marriage discourse itself. The discussions and analysis call for a more inclusive and intersectional understanding of queer rights, citizenship and intimate relations. Drawing insights from literature, this article explores the historical and socio-cultural premises of homosexual relationships. It critically looks in to the discursive burden placed on homosexual people to validate their existence by invoking evidence distinct from heteronormative frameworks. Within a heteronormative society, queer intimacies are often rendered intelligible only through demonstrable proof, thereby subjecting them to constant scrutiny and justification. The article also portrays the state’s attempts to legitimize queer bodies and desires through legal recognition, these attempts by state leads to codifying intimacy into narrow legal categories, thereby producing a hierarchy of legitimacy that privileges normative partnerships and marginalizes non-conforming relationalities. This process, paradoxically, may render some queer lives even more precarious under the guise of inclusion. These nuanced positions, often sidelined in both mainstream media and dominant queer activism, highlight the need to reimagine the desires or intimacies beyond legal assimilation.